Extensions to Tiered Coalition Formation Games - Nathan Arnold; Judy Goldsmith; Sarah Snider (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
In 2017, Siler introduced Tiered Coalition Formation Games (TCFGs), inspired by the tiered organization of Pokémon characters on a fan-based website, Smogon. Siler showed that, for a natural notion of agent preferences, the Nash table tier lists were precisely the core stable tier lists, and provided a polynomial-time algorithm to find a Nash stable tier list. However, the tiers in that list had size one, which eliminated the intra-tier competitions that make tier lists meaningful.